Implementation, Impact, and Development of ERP Systems in The 4.0 Era: A Literature Review - Mahmuda Arpan, Safa Rifha; Akhriani, Ririn; Annisa Maknun, Andi Batari; Pontoh, Grace. T; Aini Indrijawati (JURNAL AKUNTANSI DAN KEUANGAN DAERAH, 2025)
Technological advancements, application, and system development help organizations track and improve their performance. The software system commonly used by organizations for a long time is Enterprise Resource Planning (ERP). The purpose of this study is to determine and analyze the implementation, impact, and improvement of accounting information system based ERP in the 4.0 era. This research was conducted using the Systematic Literature Review (SLR) method. This study found that ERP has a big role in the 4.0 era. Namely, the implementation of ERP systems provides benefits including increased flexibility, providing more and better quality information, and improving the quality of financial statements. The limitations in this study lie in previous research which still does not discuss the 4.0 era. So it is recommended for further research to use variables outside of this study. Keywords: ERP, implementation, impact, development accounting information system (AIS), ERP 4.0